El enfoque de los derechos humanos y las políticas públicas (2007)
The rights-based approach intends to contribute with a new vision of human rights, conceiving themas comprehensive, interdependent and complementary. Thus, this approach is superior to the traditional approach of Generations of Rights and its matching of fundamental rights only to first-generation human rights. Another characteristic of this approach to human rights is its concern about the rights’ specificmanifestation or actual materialization, as well as paying attention to minorities. This materializationtakes place through the implementation of public policies focusing on rights and with a wide participationof civil society. In this way, human rights become the benchmark and the ultimate goal for public policies,and such policies, in turn, become the optimum instrument or means to secure the fulfillment of theserights. This is how the rights-based approach may provide a perspective to guide the actions and theintervention of public authorities through the different socio-economic development plans and programs.